S. polyanthum leaves aqueous extracts as potential antihypertensive agent in spontaneous hypertensive rat model - Baharun, Bibi Nur Bazlini (2018)
Hypertension remains a major modifiable risk factor for cardiovascular disease (CVD). One of the local medicinal plant reported could be potentially served as antihypertensive agent is Syzygium polyanthum (serai kayu). Therefore, this study aims to evaluate the aqueous extract of S. polyanthum (AESP) as potential antihypertensive agent in spontaneous hypertensive rat model (SHR). This study employed 35 male SHR which then was further divided into 5 group; untreated-SHR, Losartan-treated, 3 AESP-treated with different dosages (1500 mg/kg,1750 mg/kg and 2250 mg/kg) along with 7 male WKY rats as normal control orally treated for 92 days. The effects of AESP were evaluated by measuring the reduction of systolic blood pressure (SBP) using non-invasive tail-cuff method. Meanwhile, morphology changes of the thoracic aorta and kidney was assessed using haematoxylin & eosin staining observation as well as Scanning Electron Microscope (SEM). Renal function test (RFT), antioxidant activity (FRAP) and total phenolic content (TPC) of AESP were also evaluated in this study. The results of the study suggested that, all three doses of AESP significantly reduced SBP of SHR rat comparable to normal WKY rat at 8th week, while at 10th week comparable to Losartan-treated group. At the end of 12th week, SBP of the AESP-treated group are similar to WKY group and lower than Losartan-treated group. The lowest dosage (1500mg/kg) was chosen as the effective dose. In addition, AESP also manage to improve the morphology structure of thoracic aorta and kidney of the rat. The morphology improvement of the organ of interest structure can be attributed to the high antioxidant property and phenolic compound found in AESP. There was no significant difference in RFT among the experimental groups. This suggested that despite there were significant morphological changes on the kidney due to 3 months effects of hypertension, their function remains intact. Thus, this study strongly suggests that S. polyanthum possess potential as antihypertensive agent and can alleviate the effect of end organ damage in hypertension.